The Effect of Human Resource Quality, Work Professionalism, and Commitment on Employee Performance: A Case Study At PT Pelindo Multi Terminal - Eriza, Zulfira; Prayudi, Ahmad; Syahrial, Herry (Journal of Management and Business Innovations, 2025)
This paper examines the relationship between human resource quality, work professionalism, and employee commitment on performance at PT Pelindo Multi Terminal Branch Belawan. Using a quantitative approach with a full sample of 50 employees, the study found that human resource quality (β = 0.316), professionalism (β = 0.218), and commitment (β = 0.477) each have a significant positive effect on performance. These results highlight the importance of improving employee capabilities, encouraging professional behavior, and fostering loyalty to enhance operational success in port activities. Keywords: Commitment, Employee Performance, HR Quality, Professionalism